New approaches and error assessment to snow cover thickness and density using air temperature data at different heights - García-Maroto, Diego; Durán Montejano, Luis; Pablo Hernández, Miguel Ángel de (Science of The Total Environment, 2024)
Snow poles are inexpensive systems composed of a wooden mast with temperature sensors affixed at varying heights with the purpose of estimating the snow depth. They are frequently utilised in cold, remote regions where the maintenance of complex monitoring instruments becomes impractical. In this study, snow cover thickness is determined using different methods, based on the thermal behaviour of air temperature measured by a snow pole on Deception Island, Antarctica. The methods are compared to high-resolution measurements of snow depth obtained using an ultrasonic sensor at the same site. A new modified method is proposed and shown to give the best results. Errors and sensitivity to chosen thresholds of the various methods have been compared. Sensitivity tests have been also conducted to evaluate the impact of missing data from some of the sensors. Finally, the insulating effect on the thermal signal produced by the snow is used to obtain information on the snowpack density. Promising results have been found from this effort, opening new possibilities for the usage of snow poles and may lead to future studies. Government of Spain, Ministry of Economy and Competitivity Spanish Polar Committee by contracts PERMATHERMAL Proyectos de Generación de Conocimiento 2022, Ministry of Science and Innovation, Spain Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub